2013
DOI: 10.1002/da.22152
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Quality of Life, Functioning, and Depressive Symptom Severity in Major Depressive Disorder Comorbid With Panic Disorder Before and After Ssri Treatment in the Star*d Trial

Abstract: Background Panic disorder (PD) is highly comorbid with major depressive disorder (MDD) with potential impact on patient-reported outcomes of quality of life (QOL), functioning, and depressive symptom severity Methods Using data from the sequenced treatment alternatives to relieve depression (STAR*D) trial, we compared entry and post-SSRI-treatment QOL, functioning, and depressive symptom severity scores in MDD patients with comorbid PD (MDD+PD) to MDD patients without PD (MDDnoPD). We also compared pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
1
9
1
1
Order By: Relevance
“…Compared to Western studies involving MDD patients10193233, the 71.7% prevalence of comorbid GAD that we found in this study was higher. Our prevalence estimate was also higher than the one reported in a Chinese study by Gao et al 34,.…”
Section: Discussioncontrasting
confidence: 94%
“…Compared to Western studies involving MDD patients10193233, the 71.7% prevalence of comorbid GAD that we found in this study was higher. Our prevalence estimate was also higher than the one reported in a Chinese study by Gao et al 34,.…”
Section: Discussioncontrasting
confidence: 94%
“…For individuals who were abstinent, their QLES‐Q‐SF scores were higher by 6.78 points (12%), correlating with greater than one standard deviation of improvement as seen in community samples (SD = 11.3%). This is a clinically meaningful improvement as supported by previous studies examining changes in QLES‐Q‐SF during treatment for major depressive disorder . Individuals with CUD, by definition, are having impairment across many areas of their life as a result of their cannabis use.…”
Section: Discussionsupporting
confidence: 63%
“…Correlating reduction in opioid use with changes in functioning can help guide an overall treatment strategy. Indeed, research in depression and anxiety disorders 52 has shown that quality of life assessments can add an important dimension to overall evaluation of patients’ treatment response, as symptom measures do not always present a complete picture of a patient’s overall functioning or recovery. Furthermore, brief, widely-used measures of health-related quality of life such as the SF-36 enable comparisons of these factors between different patient populations that can inform both clinical treatment selection and policy decisions about the allocation of health care resources.…”
Section: Discussionmentioning
confidence: 99%